GEOMETRIC AND MORPHOLOGIC EVOLUTION OF NORMAL FAULT PLANES AND TRACES FROM 2D TO 4D DATA - Marchal D.; Guiraud M.; Rives T. (My University, 2003)
The detailed 3D geometry of normal fault planes is described and analysed using datasets from outcrop studies (2D), seismic surveys (3D) and analogue models (4D). Different geometric configurations of simple isolated normal faults are studied by reference to processes of normal fault propagation. When a normal fault propagates without interacting with other fault zones, the entire border of the principal plane displays characteristic connected secondary structures. These secondary structures cause bifurcations of the principal fault terminations. The along-strike terminations of the principal plane display typical bifurcation configurations ('ear geometry'). The orientation of the bifurcations depends on the vertical direction of propagation (downwards and/or upwards). The along-dip terminations display en echelon secondary fault planes linked to the principal plane and are described as 'lobate geometry'. A 3D genetic model of isolated normal fault geometry is proposed with a new general terminology for the secondary structures. When two isolated normal faults propagate towards each other and overlap, the two principal planes connect up via a relay fault. The resulting geometry is a longer fault exhibiting a characteristic undulation with two inactive branches.
Keywords: NORMAL FAULT; GEOMETRY; TERMINATION; BIFURCATION; PROPAGATION